ULAMA AL-JAWWI DI ARAB SAUDI DAN KEBANGKITAN UMAT ISLAM DI INDONESIA - Mukani Mukani (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
The Indonesia muslim movement of the Dutch colonial period had closely related with Jawwah Community or Ulama Al-Jawwi in Saudi Arabia. This term refers to the development of students of Southeast Asia. Snouck Hurgronje, the adviser of the Dutch government, visited Mecca from 1884 to 1885. In the XIII century AD, intellectual relationship was began, it was then responsible for disseminating Islamic thought developing in Mecca to Indonesia. After they returned to their homeland, they became intellectual actors who introduced new ideas about the Islamic teachings of society, especially in evoking the nationalism spirit towards independence. Despite the the Netherlands terror, the Jawwah Community has served as